Preliminary results on the effect of seeding methods on production and botanical composition of perennial mixtures of alfalfa-grasses - Zoghlami A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In order to get perennial mixtures of legume-grasses highly yielding, suitable and with better nutritive value, a serial of trials were undertaken since 1992 at Tunis, under semi-arid conditions. These trials aimed firstly to compare the production and the botanical and chemical composition of some alfalfa-grasses combinations and secondly to compare the production and behaviour of these combinations to their pure stands. Results of the first serial of trials (1991-1993) showed that there was no significant difference between the 3 tested mixtures in terms of total annual production and chemical and botanical composition (Zoghlami et al., 1995). At the contrary, seasonal production was different from one combinaison to another. According to these results, 4 combinations were tested and compared to their pure stands (1993-1996). Results showed that mixtures were higher than pure stands and had a good yield distribution in the year (Zoghlami et Seklani, 1997).
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)